2021
DOI: 10.3389/fonc.2021.784924
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Histopathological Features on the Prognosis of Oral Squamous Cell Carcinoma: A Comprehensive Review and Meta-Analysis

Abstract: ObjectiveOver many decades, studies on histopathological features have not only presented high-level evidence of contribution for treatment directions and prognosis of oral squamous cell carcinoma (OSCC) but also provided inconsistencies, making clinical application difficult. The 8th TNM staging system of OSCC has acknowledged the importance of some histopathological features, by incorporating depth of invasion (DOI) to T category and extranodal extension (ENE) to N category. The aim of this systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 80 publications
3
53
3
Order By: Relevance
“…Histological characteristics of the tumor and its surrounding tissues play an important role in the diagnosis of tumor biopsies, and are becoming increasingly important in prognostication. Such features include depth of invasion and perineural invasion, which are currently included in the pathology report 10 and have been recently reviewed in studies of heterogenous subsites of oral squamous cell carcinoma 10–12 . Furthermore, many HE‐related prognostic markers have been introduced in recent studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological characteristics of the tumor and its surrounding tissues play an important role in the diagnosis of tumor biopsies, and are becoming increasingly important in prognostication. Such features include depth of invasion and perineural invasion, which are currently included in the pathology report 10 and have been recently reviewed in studies of heterogenous subsites of oral squamous cell carcinoma 10–12 . Furthermore, many HE‐related prognostic markers have been introduced in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Such features include depth of invasion and perineural invasion, which are currently included in the pathology report 10 and have been recently reviewed in studies of heterogenous subsites of oral squamous cell carcinoma. [10][11][12] Furthermore, many HE-related prognostic markers have been introduced in recent studies. Although these have shown good prognostic value for early-stage OTSCC, they are not included in clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis, the largest of its kind to date, has found a strong association between the positive tumour margin and the risk of overall survival (OS), disease-specific survival (DSS) and recurrence. 10 50 eligible studies with pooled analyses of surgical margins were considered. These included 63 470 patients (31 studies), with OS data, 20 680 patients 19studies with DSS data and 15 300 patients (25 articles) with data for disease-free survival (DFS).…”
Section: Cle Ar Vs Clos E or Involved Marg In Smentioning
confidence: 99%
“…Most published studies have compared clear margins (>5 mm of normal tissue) against a combination of close (1–4 mm of normal tissue) and involved (<1 mm of normal tissue) margins. In the recent large meta‐analysis, 10 20 studies did not define the margin distance but instead grouped tumour resections as those with either clear margins or close/involved margins. Pooled analyses confirmed that one or more involved resection margins were significantly associated with worse OS, DSS and DFS, irrespective of the amount of normal tissue from the tumour edge in the rest of the specimen 10 …”
Section: Clear Vs Close or Involved Marginsmentioning
confidence: 99%
See 1 more Smart Citation